Pemanfaatan Artificial Intelligence (AI) untuk Ide Penciptaan Karya Seni Berbahan Serbuk Kayu di CV. Rendy Hendicraft - Soeheri, Soeheri; Setiawan, Adil; Nasution, M. Irfan Aldy; Akbar, Muhammad Barkah (Publikasi Pengabdian Masyarakat, 2024)
The utilization of Artificial Intelligence (AI) in the creative industry has opened new opportunities to enhance innovation and efficiency. This study aims to explore the use of AI as a tool to generate creative ideas for wood powder-based art at CV. Rendy Hendicraft. The methodology includes experiments with generative AI tools such as Flux AI, DALL-E and MidJourney to produce initial designs, followed by a selection and adaptation process by local artists. The results demonstrate that AI can generate diverse innovative design patterns, including traditional carvings, geometric abstracts, and modern-traditional hybrid elements, which are then transformed into wood powder artworks. The collaboration between AI and humans accelerates the conceptualization phase and broadens creative perspectives. However, adapting AI-generated designs to the wood powder medium requires modifications to accommodate material characteristics, such as texture and structural durability. The impacts of this initiative include increased productivity for CV. Rendy Hendicraft, product diversification, and strengthened competitiveness in the craft market. This study concludes that integrating AI into the creative process does not replace human roles but acts as an innovation catalyst supporting the sustainability of local-based creative industries.